2001
DOI: 10.1136/jnnp.71.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Highly increased CSF tau protein and decreased beta-amyloid (1-42) in sporadic CJD: a discrimination from Alzheimer's disease?

Abstract: The aim was to quantify tau protein and -amyloid (A 42) in the CSF of patients with sporadic Creutzfeldt-Jakob disease (CJD), Alzheimer's disease (AD), and controls. Double sandwich enzyme linked immunosorbent assays (ELISAs) were used for measurments. Tau was increased 58-fold in CJD and 3.5-fold in AD compared with controls, whereas A 42 was decreased 0.5-fold in both CJD and AD. A cut oV level for tau protein at 2131 pg/ml successfully discriminated CJD from AD (100% specificity and 93% sensitivity). Tau pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 14 publications
7
68
0
5
Order By: Relevance
“…to assume that there is no difference between groups despite a true difference of markers in the population. Our results, however, showing significantly lower levels of CSF p-tau 231 and t-tau in HC subjects compared to AD patients as well as extremely high t-tau values in CJD compared to other diagnostic entities are in accordance with the literature [2,3,4,7,11,15]. The main findings of our study refer to the CJD and the AD groups, i.e.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…to assume that there is no difference between groups despite a true difference of markers in the population. Our results, however, showing significantly lower levels of CSF p-tau 231 and t-tau in HC subjects compared to AD patients as well as extremely high t-tau values in CJD compared to other diagnostic entities are in accordance with the literature [2,3,4,7,11,15]. The main findings of our study refer to the CJD and the AD groups, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, a biomarker to support differential diagnosis between CJD and AD would be clinically meaningful. In cerebrospinal fluid (CSF), determination of total tau protein (t-tau) concentration is of high diagnostic value for CJD with sensitivity and specificity levels above 90% when distinguishing CJD from non-demented and demented neurological controls and AD [11,15,20,21]. T-tau levels are elevated both in CJD and AD relative to controls, but the increase is several magnitudes higher in CJD compared to AD.…”
Section: Introductionmentioning
confidence: 99%
“…As so the ratio between phosphorylated tau (p-tau) and t-tau levels (p-tau/ t-tau) was shown to improve discrimination between AD and sCJD, with lower levels in favour of the latter [5,28,32]. Reduced Ab42 CSF levels have also been reported in sCJD patients, as in AD, but mostly overlapping [17,38,39]. NSE and S-100b are elevated in sCJD patients, but do not seem to attain sufficient sensitivity and specificity for differential diagnosis [21,30,43].…”
Section: Introductionmentioning
confidence: 93%
“…Following the principle that CSF proteins reflect changes in pathological brain conditions, elevated levels of these proteins are used as surrogate markers for neuronal damage (14-3-3, tau, NSE) or astrocytic gliosis (S-100b). CSF total tau (t-tau) reaches extremely high levels in sCJD, probably reflecting the extent of the neurodegenerative process, and has been reported to be clinically useful, with sensitivity and specificity for sCJD similar to the 14-3-3 test [17,22,38,39]. Unlike what happens in Alzheimer's disease (AD), hyperphosphorylation of tau and formation of neurofibrillary tangles (NFTs) do not occur in sCJD.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies demonstrated that the levels of CSF Aβ42 in AD are decreased compared with controls [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] . CSF Aβ42 can differentiate AD from controls with 89% sensitivity and 90% specificity [51] .…”
Section: Csf Aβ42 As a Biomarker Of Admentioning
confidence: 99%